Nonlinear Transport and Magnetic/Magneto-Optical Properties of Cox(MgF2)100-x Nanostructures - Sergey A. Ivkov; Konstantin A. Barkov; Evelina P. Domashevskaya; Elena A. Ganshina; Dmitry L. Goloshchapov; Stanislav V. Ryabtsev; Alexander V. Sitnikov; Pavel V. Seredin (Applied Sciences, 2023)
The aim of this work was to comprehensively study the effect of the variable atomic composition and structural-phase state of Cox(MgF2)100-x nanocomposites on their nonlinear transport and magnetic/magneto-optical properties. Micrometer-thick nanocomposite layers on glass substrates were obtained by means of ion-beam sputtering of a composite target in the argon atmosphere in a wide range of compositions (x = 16–59 at.%). Using a low metal content in the nanocomposite, magnesium fluoride was kept in the nanocrystalline state. As the metal content increased, nanocrystalline cobalt was formed. The value of the resistive percolation threshold, xper = 37 at.%, determined from the concentration dependences of the electrical resistance of the nanocomposites coincided with the beginning of nucleation of the metallic nanocrystals in the MgF2 dielectric matrix. The absolute value of the maximum negative magnetoresistive effect in the nanocomposites was 5% in a magnetic field of 5.5 kG at a Co concentration of x = 27 at.%.